Effectiveness Test of Minimum Inhibitory Concentration (MIC) and Minimum Bacterial Concentration (MBC) of Papaya Latex Extract ( Carica papaya. L ) Against Pseudomonas aeruginosa Bacteria - herman herman; Fendy Prasetyawan; Anis Akhwan Dhafin; Achmad Wahdi (Institut Kesehatan YARSI Mataram, 2025)
This study aims to test the effectiveness of papaya latex extract (Carica papaya L.) in inhibiting and killing Pseudomonas aeruginosa bacteria using the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) methods. Papaya latex extract was extracted using the percolation method and tested at various concentrations, namely 50%, 25%, 12.5%, 6.25%, and 3.125% and 1,4%. The MIC test results showed that a concentration of 12.5% was able to inhibit bacterial growth, while concentrations of 25% and 50% effectively killed the bacteria completely. The SPSS test showed a significant difference between concentrations (p < 0.05) on bacterial growth, with a concentration of 25% as the most effective in killing bacteria. Based on these results, papaya latex extract has good antibacterial potential, especially at concentrations ≥ 25%, and can be used as an alternative in the development of natural antibacterial agents. ABSTRAK Penelitian ini bertujuan untuk menguji efektivitas ekstrak getah pepaya (Carica papaya L.) dalam menghambat dan membunuh bakteri Pseudomonas aeruginosa dengan menggunakan metode Kadar Hambat Minimum (KHM) dan Kadar Bunuh Minimum (KBM). Ekstrak getah pepaya diekstraksi dengan metode perkolasi dan diuji pada berbagai konsentrasi, yaitu 50%, 25%, 12,5%, 6,25%, 3,125% dan 1,4%. Hasil uji KHM menunjukkan bahwa konsentrasi 12,5% mampu menghambat pertumbuhan bakteri, sementara konsentrasi 25% dan 50% efektif dalam membunuh bakteri secara total. Uji SPSS menunjukkan adanya perbedaan yang signifikan antar konsentrasi (p < 0,05) terhadap pertumbuhan bakteri, dengan konsentrasi 25% sebagai konsentrasi yang paling efektif dalam membunuh bakteri. Berdasarkan hasil ini, ekstrak getah pepaya memiliki potensi antibakteri yang baik, terutama pada konsentrasi ≥ 25%, dan dapat dijadikan alternatif dalam pengembangan agen antibakteri alami.